Alfred Corn, translator. The Duino Elegies, by Rainer Maria Rilke. Norton, 2021. - Jeremy Glazier (Studies in 20th & 21st Century Literature, 2021)
Review of Alfred Corn, translator. The Duino Elegies, by Rainer Maria Rilke. Norton, 2021. 112 pp.
Keywords: translation; Rilke; Duino Elegies; German poetry; modernism